1997
DOI: 10.1177/002199839703101102
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Ply Cracking in Cross-Ply CFRP Laminates—Initiation or Propagation Controlled?

Abstract: The initiation and propagation stages of transverse ply cracking in crossply CFRP laminates under quasi-static loading have been studied using laminates with a range of transverse ply thicknesses. Specimens of two types have been tested-coupons with polished edges and coupons with defects (notches) introduced into the transverse ply prior to testing. Detailed observations of crack propagation across the transverse ply thickness and width have been made, along with measurements of crack density and residual pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…The crack spacing is not necessarily uniform and therefore, delamination length is not identical for all of matrix cracks. It was observed that delamination initiation and growth are the consequences of matrix cracking saturation and this is in agreement with many experimental findings as indicated in 5,8,14 . Similar to bisecting method, the critical crack density is decreased with increasing the number of 90 o layers.…”
Section: -2) [90 N /0] S Laminatessupporting
confidence: 90%
“…The crack spacing is not necessarily uniform and therefore, delamination length is not identical for all of matrix cracks. It was observed that delamination initiation and growth are the consequences of matrix cracking saturation and this is in agreement with many experimental findings as indicated in 5,8,14 . Similar to bisecting method, the critical crack density is decreased with increasing the number of 90 o layers.…”
Section: -2) [90 N /0] S Laminatessupporting
confidence: 90%
“…the applied mechanical strain) of the h = 120 nm coating on 12 lm substrate amounted to e a = 1.3 ± 0.1% regardless of the temperature within 26-150°C range. Yanaka et al [37] interpreted this result as a proof of strength criterion for coating fracture; this criterion corresponds to the case of crack initiationcontrolled failure according to [38,39]. However, the COS data are amenable also to fracture mechanics, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…They occur relatively early in the case of transverse loading, but very late in the case of shear loading. They generally initiate at the edge of the samples, then propagate in a stable or unstable way towards the core [10] depending on the type of ply (the well-known thickness effect [11]) and on the loading (static or cyclic [12]). …”
Section: Degradation Mechanisms On the Ply's Scalementioning
confidence: 99%